2012
DOI: 10.1016/j.jpha.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Capture of cervical exfoliative cells on a glass slide coated by 3-glycidyloxypropyl trimethoxysilane and poly-L-lysine

Abstract: A new modification method for glass slides was developed and applied to make ThinPrep Pap smears, in order to increase the adhesion ability of cervical exfoliative cells. 3-glycidyloxypropyl trimethoxysilane (GOPS) was coated on the glass slides firstly on the slides, then poly-L-lysine (PLL) was covalently modified onto the above epoxy-terminated slides to form GOPS-PLL double decorated slides. The modified slides were characterized using X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Of note, the roughness of the SiC surface (rms: 1.66 nm) increased after silanization (rms: 2.52 nm). Xing et al . reported that the liquid deposition of GOPTS on glass did indeed increase the roughness of the substrate but likewise also the number of adhesive cells grown on top of this monolayer; our results are aligned with this finding.…”
Section: Resultssupporting
confidence: 91%
“…Of note, the roughness of the SiC surface (rms: 1.66 nm) increased after silanization (rms: 2.52 nm). Xing et al . reported that the liquid deposition of GOPTS on glass did indeed increase the roughness of the substrate but likewise also the number of adhesive cells grown on top of this monolayer; our results are aligned with this finding.…”
Section: Resultssupporting
confidence: 91%
“…This work provides an efficient method for the preparation of organic mixed ionic–electronic conductor films stable in aqueous environments that does not compromise the electronic properties. While this work focused on PEDOT:PSS on various substrates (glass, silicon wafer, gold), the same functionalization method could be extended to other organic semiconductors containing nucleophilic substituents that can react with epoxides, such as carboxyl, and amine , functional groups, to reduce substrate delamination and increase the mechanical stability of the device for bioelectronics applications in aqueous environments.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of blending GOPS with PEDOT:PSS, only the surface of the substrate is functionalized with GOPS to introduce a silane monolayer with epoxy groups before spin-coating PEDOT:PSS (Figure 1c). GOPS is commonly utilized in biomedical applications as an adhesive monolayer for the immobilization of proteins, 38 DNA, 39 and cervical exfoliative cells, 40 but these monolayers had surprisingly never been explored for the deposition of PEDOT:PSS. Films obtained by surface functionalization were compared to those obtained by blending and showed similar operational stability in water under passive conditions and electrochemical cycling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the culture system, the most easily adherent cells are fibroblasts, followed by glial cells, and finally neurons 22 . PLL encapsulation can improve the adhesion ability of cells 23,24 . Therefore, we assume that PLL has different adhesion ability to different cells and will separate fibroblasts and other heterocytic cells.…”
Section: Discussionmentioning
confidence: 99%